Free Fatty Acids in Bone Pathophysiology of Rheumatic Diseases - Frommer, Klaus W.; Hasseli, Rebecca; Schäffler, Andreas; Lange, Uwe; Rehart, Stefan; Steinmeyer, Jürgen; Rickert, Markus; Sarter, Kerstin; Zaiss, Mario M.; Culmsee, Carsten; Ganjam, Goutham; Michels, Susanne; et al. (Frontiers in Immunology, 2019)
Obesity - in which free fatty acid (FFA) levels are chronically elevated - is a known risk factor for different rheumatic diseases and obese patients are more likely to develop osteoarthritis (OA) also in non-weight-bearing joints. These findings suggest that FFA may also play a role in inflammation-related joint damage and bone loss in rheumatoid arthritis (RA) and OA. Therefore, the objective of this study was to analyze if and how FFA influence cells of bone metabolism in rheumatic diseases. When stimulated with FFA, osteoblasts from RA and OA patients secreted higher amounts of the proinflammatory cytokine IL-6 and the chemokines IL-8, GRO-alpha and MCP-1. RANKL, OPG and osteoblast differentiation markers were not influenced by FFA. Mineralization activity of osteoblasts correlated inversely with the level of FFA-induced IL-6 secretion. Expression of the Wnt signaling molecules, axin-2 and beta-catenin, was not changed by palmitic acid (PA) or linoleic acid (LA), suggesting no involvement of the Wnt signaling pathway in FFA signaling for osteoblasts. On the other hand, TLR4 blockade significantly reduced PA-induced IL-8 secretion by osteoblasts, while blocking TLR2 had no effect. In osteoclasts, IL-8 secretion was enhanced by PA and LA particularly at the earliest time point of differentiation. Differences were observed between the responses of RA and OA osteoclasts. FFA might therefore represent a new molecular factor by which adipose tissue contributes to subchondral bone damage in RA and OA. In this context, their mechanisms of action appear to be dependent on inflammation and innate immune system rather than Wnt-RANKL pathways.